Effect of Manures and Fertilizers on Varieties of Lentil at Tikapur, Kailali - Sharma, Rakash; Bohara, Binod; Rajbanshi, Devraj (Far Western Review, 2025)
Lentil, key exported pulse crop of Nepal has huge scope of improving its productivity in Far Western province, with slight modification in input use. To study the effect of different fertilizers on growth and yield of two commonly grown varieties of lentil, an experiment was conducted in Tikapur Kailali at Agronomy farm of Far Western University by using factorial RCBD. The factors considered were a. Varieties (Local masuro and Khajura masuro-2) and b. Organic fertilizers (farmyard manure, vermicompost, panchagavya and Control-no organic fertilizers). The results revealed no significant differences in most of the parameters except for shoot length, root length and days to flowering between the two commonly grown varieties compared in the study. Statistically, Khajura masuro-2 showed greater shoot length, smaller root length, and early flowering than local variety. Significant delay in maturity was observed with application of Panchagavya, followed by vermicompost which was statistically similar to farmyard manure. Statistically higher pod count per plant and grains per plant were observed with vermicompost over all the applications. The Control yielded significantly smaller length of shoot and correspondingly lesser grain yield indicating the importance of organic applications for improved growth and yield of lentil.